Mathematical modelling and scientific computation : International conference, ICMMSC 2012, Gandhigram, Tamil Nadu, India, March 16-18, 2012. Proceedings - Uthayakumar, R.; Balasubramaniam, P. (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the International Conference on Mathematical Modelling and Scientific Intelligence, ICMMSC 2012, Gandhigram, Tamil Nadu, India, in March 2012. The 62 revised full papers presented were carefully reviewed and selected from 332 submissions. The papers are organized in two topical sections on mathematical modelling and on scientific computation.